Prevention of the Spread of the COVID-19 Virus with an Online to Offline Shopping System with an Independent Self-Service Concept using a Miniature Solar-Powered Mobile Market - Anantha Zakharia; Irvan Hermala; Putie Maharani (PT FORMOSA CENDEKIA GLOBAL, 2022)
The COVID-19 pandemic has destroyed the economy in Indonesia since March 2020, where all regions implemented Large-Scale Social Restrictions (PSBB) and Micro-Scale Social Restrictions (PSBM). This causes people to reduce their shopping activities and limit business activities by the local government. The participation of universities is highly expected in assisting economic recovery, so that economic turnover activities can continue without increasing the number of Covid-19 sufferers. In this case, universities provide solutions in the field of renewable energy as a source of electricity to support the efficiency of the prototypes produced. This activity was carried out by students and lecturers as a form of community service. Where the concept offered is online to offline to maintain shopping loyalty. Consumers can make transactions by selecting product quality, tasting the product, and tasting the product first and they do it in front of their house in the form of a solar-powered mobile market. It is hoped that this activity can support the normal course of the economy as before the pandemic occurred.